Distress Tolerance as a Predictor of Adherence to a Yoga Intervention: Moderating Roles of BMI and Body Image. (January 2016) - Baird, Scarlett O.; Hopkins, Lindsey B.; Medina, Johnna L.; Rosenfield, David; Powers, Mark B.; Smits, Jasper A. J.
This study tested whether distress tolerance, body image, and body mass index (BMI) predicted adherence to a yoga intervention. Participants were 27 women who participated in a yoga intervention as part of a randomized controlled trial. Attendance and distress tolerance were assessed weekly, and body image and BMI were measured at baseline. Multilevel modeling revealed a three-way interaction of distress tolerance, BMI, and body image ( p < .001). For participants with few body image concerns, distress tolerance was positively associated with adherence regardless of BMI ( p = .009). However, for those with poor body image, increases in distress tolerance were associated with increases in adherence among overweight participants ( p < .001) but lower adherence among obese participants ( p = .007). Distress tolerance may be implicated in adherence to a yoga intervention, although its effects may be dependent on body image concerns, BMI, and their interaction. Research and clinical implications are discussed.